Structural damage analysis of CRTS Ⅱ slab track with various interface models under temperature combinations. (April 2022) - Zhou, Rui; Zhu, Xuan; Huang, Jiaqi; Zhou, Haijun; Liu, Hanlin; Ma, Cong; Zhang, Lihai
Highlights: Six nonlinear FEMs were studied to identify thermal behaviors of CAM and joint under various temperature conditions. The CZM and CDPM could effectively simulate the interlaminar debonding and damage behavior development in CRTS II track. Both the displacement and stress of the structure increase with an increase in overall temperature or temperature gradient. The damage factor of the interface between the CAM layer and track slab are vulnerable to the overall temperature. Abstract: Under temperature loading, the contact interface of cement asphalt mortar (CAM) layer and T-shaped joint are two vulnerable components of China Railway Track System type II (CRTS II) slab ballastless track. The purpose of this study is to develop six types of three-dimensional (3D) nonlinear finite element (FE) models for investigating the thermal behaviors of CAM and T-shaped joint under various temperature conditions. This was achieved by modelling CAM and T-shaped joint using cohesive zone model (CZM) and concrete damaged plasticity model (CDPM), respectively. Using five CRTS II slab tracks on a simple-supported box girder as a case study, the displacement and stress responses of the track structure were investigated and compared under six cases of overall temperatures and temperature gradients, respectively. Results show that CZM and CDPM have the capabilities of simulating the interlaminar debonding and damage behavior development in CRTS II track under various temperatures conditions. The combination of CZM and CDPM could provide the worst damage scenarios, and the CDPM of the joint could significantly reduce the structure responses. In addition, the increase of overall temperature together with temperature gradient could significantly increase the deformation and stress in CAM layer, and the influence of the magnitude of overall temperature is more obvious than that of temperature gradient.